Estudio De Caso: Intervención Psicopedagógica Para Desarrollar Las Áreas Conductuales Básicas En Un Niño Con Trastorno Del Espectro Autista, Del Sexto Grado De La Escuela De Educación Básica Especializada Ciudad De Loja N° 1, Periodo 2020 – 2021 - Marchena Ortiz, Karen Cecilia (2023)
The current curricular integration essay called "Psychopedagogical Intervention to develop the basic behavioral areas in a child with Autism Spectrum Disorder, from the sixth grade of Loja City Specialized Basic Education School No. 1, Academic Period 2020 - 2021" it intended to identify the current situation of the child with ASD from the family and social environment and to describe the realities of the learning process for the development of skills in the basic behavioral areas with a focus on behavior modification from the different environments of the child with Autism Spectrum Disorder, this study had a qualitative approach based on a case study, of a descriptive cross-sectional type, using techniques and instruments to collect data such as participatory observation, semi-structured interviews; the Conners Scale for parents and teachers and the Inventory of Academic Conduct Skills and Verbal Conduct. From the obtained results: the current situation of the child, the diagnosis remains ASD grade 3; From the family and social environment, it can be observed aggressive behaviors, anxiety, scholar irritability, low tolerance for frustration and non-verbal communication gesturalized with stereotyped movements. The psychopedagogical intervention to strengthen skills in behavioral areas or basic repertoires was planned in sessions for 3 months (75 sessions) based on behavior modification techniques. Goals were achieved in the skills learning processes in the behavioral areas or basic repertoires through the application of the Psychopedagogical Intervention program, with the intervention of the family and social environment. Finally, there were stablished conclusions and recommendations meant at the promotion and application of the "Beyond Words" Program, it allows the understanding and intervention of more children with ASD within the described areas and at different levels.